2013
DOI: 10.1093/toxsci/kft014
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Circulating RNA: A Window into Systems Toxicology

Abstract: Adverse effects caused by therapeutic drugs are a serious and costly health concern. Despite the body's systemic responses to therapeutics, the liver is often the focus of damage and is usually the focus of studies of toxic effects due to its active roles in the metabolism of xenobiotics. It is extremely difficult, however, to assess systemic responses with currently available methods. Comprehensive cataloging of cell-free circulating RNAs using next-generation sequencing technology may open a window to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Some in vivo studies support the initial finding that xenomiRs are present in body fluids of humans and other animals, however at a very low expression level (Wang et al 2012(Wang et al , 2013. The most highly abundant Brassica oleracea MIR172 was found in stomach, intestine, serum, and feces of mice that were fed plant RNA extracts.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Some in vivo studies support the initial finding that xenomiRs are present in body fluids of humans and other animals, however at a very low expression level (Wang et al 2012(Wang et al , 2013. The most highly abundant Brassica oleracea MIR172 was found in stomach, intestine, serum, and feces of mice that were fed plant RNA extracts.…”
Section: Introductionmentioning
confidence: 61%
“…These data sets included 215 serum and plasma samples and 37 exosome samples, since these are body fluids that have previously been described to contain xenomiRs (Wang et al 2012(Wang et al , 2013Zhang et al 2012;Liang et al 2015). We also selected 180 samples of cerebrospinal fluid (CSF), which is separated from the bloodstream by the brain-blood barrier (BBB), which unprotected small RNAs are unlikely to cross (Pardridge 2005;Boudreau et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, arsenicals can release Fe by the activation of the enzyme heme-oxygenase (HO-1) (Albores et al, 1989). Negishi et al (2013) reported that the adverse effects of exposure to diphenyl arsenic acid (DPAA) in the drinking water during development could be due to an increase in HO-1 in the cerebellar astrocytes. Previously, Ahmad et al (2000) suggested the direct reduction of Ft Fe by dimethyl arsenic acid (DMAIII) as the predominant pathway, and that DMAIII and AH --mediated Fe-release from Ft (not via O 2ˉ) also may be a significant route in vivo.…”
mentioning
confidence: 99%
“…Subsequent studies in mice have greatly expanded our understanding of the transcriptomic changes that occur in response to APAP exposure (Coen et al, 2004;Liu et al, 2003;Reilly et al, 2001a, Ruepp et al, 2002Wang et al, 2013;Welch et al, 2006;Williams et al, 2004;Tachibana et al, 2011). The consensus from these studies is that toxic doses of APAP lead to the increased expression of stressresponsive genes involved in heat shock protein expression, cell cycle-response, inflammatory-response, cell signaling, and cell metabolism.…”
Section: Introductionmentioning
confidence: 99%